2014
DOI: 10.1118/1.4890101
|View full text |Cite
|
Sign up to set email alerts
|

Directional fractal signature methods for trabecular bone texture in hand radiographs: Data from the Osteoarthritis Initiative

Abstract: The AVOT method is well suited for the analysis of bone texture in hand radiographs and it could be potentially useful for early detection and prediction of hand OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…It was suggested that hand joints with radiographic OA exhibit lower distal FDs as compared to the joints without OA 4 . In our previous study, mean ± standard deviation values of 2.640 ± 0.062 and 2.691 ± 0.061 were reported for FD Sta for OA and non-OA joints respectively 4 . These values fall into the lowest tertile group (T1) of FD Sta .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that hand joints with radiographic OA exhibit lower distal FDs as compared to the joints without OA 4 . In our previous study, mean ± standard deviation values of 2.640 ± 0.062 and 2.691 ± 0.061 were reported for FD Sta for OA and non-OA joints respectively 4 . These values fall into the lowest tertile group (T1) of FD Sta .…”
Section: Discussionmentioning
confidence: 99%
“…Each TB texture ROI was quantified by means of four fractal texture parameters calculated using the AVOT method 4…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) A particular type of fractal analysis is fractal signature analysis (FSA), which is a computerized textural analysis method used to measure vertical and horizontal trabeculae based on the fractal dimensions of the bone structure over a range of trabecular widths. (6-8) FSA has been previously applied for bone architecture measurements and disease progression using radiographs in cases of knee osteoarthritis, (9)(10)(11)(12)(13)(14) osteoporosis treatment response after administration of risedronate, (15) hand osteoarthritis, (16) and hip osteoarthritis. (17) Furthermore, differences in fractal signatures in RA radiographs among three types of bone conditions, namely normal, osteopenic, and eroded bone, have also been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…However, measures of MRI-detected cartilage thickness was demonstrated superior in sensitivity to change compared to the two radiographic methods [13], further supporting the need to include MRI in longitudinal OA studies. OA, which could be potentially useful for early detection and prediction of hand OA [18].…”
Section: Conventional Radiographymentioning
confidence: 99%